Odpowiedzi

Najlepsza Odpowiedź!
2009-12-30T15:53:16+01:00
X+3(x-2)=-22
x+3x-6=-22
4x=16
x=-4

5x-2(x+3)=9
5x-2x-6=9
3x=15
x=5

4(2x+3)-5=-3
8x+12-5=-3
8x=-10
x=-1,25

2(x+1)+5x=16
2x+2+5x=16
7x=14
x=2

-4x-3(2x+1)=7
-4x-6x-3=7
-10x=10
x=-1
2009-12-30T15:55:57+01:00
X+3(x-2)=-22
x+3x-6=-22x
4x-6=-22
4x= -22+6
4x= -16/4
x=-4

5x-2(x+3)=9
5x-2x-6=9
3x-6=9
3x=9+6
3x=15/3
x=5

4(2x+3)-5=-3
8x+12-5=-3
8x= -3-12+5
8x= -10/8
x= - 5/4
x=-1,25

2(x+1)+5x=16
2x+2+5x=16
7x=16-2
7x=14/7
x=2

-4x-3(2x+1)=7
-4x-6x-3=7
-10x=7+3
-10x=10/-10
x=-1
2009-12-30T15:57:32+01:00
X+3(x-2)=-22
x+3x-6 =-22
4x =-22+6
4x=-16/:4
x=-4

5x-2(x+3)=9
5x-2x-6=9
3x=15/:3
x=5

4(2x+3)-5=-3
8x+12-5=-3
8x=-10/:8
x=-1,25 = -1¼

2(x+1)+5x=16
2x+2+5x=16
7x=14/:7
x=2

-4x-3(2x+1)=7
-4x-6x-3=7
-10x=10/:(-10)
x=-1